PENGARUH PELATIHAN, KEPRIBADIAN EKSTRAVERSI DANKEPRIBADIAN KETELITIAN TERHADAP KINERJA KARYAWAN BAGIAN MEKANIK - ICHWAN M, ACHMAD (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract:Aspects of human resources is still in the spotlight for the company to remain able to survive or even thrive. One form a human resource development is training. In addition, extraversion and conscientiousness shaping patterns of behavior and how they use it in their work. This study aimed to analyze the effect of training, extraversion, and conscientiousness on employee performance precision mechanical parts on PT X Surabaya. With a population of 53 mechanics at 5 Branchs of PT X. There are 53 employees in the sample. While the statistical analysis method used is the method of multiple linear regression analysis. The results is that training had no significant effect on the performance, extraversion no significant effect on the performance, and conscientiousness significantly influence employee performance. Simultaneously, training, extraversion, and conscientiousness significant effect on the performance of employees. Keyword: training, extraversion, conscientiousness and employee performance.